(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Japanese Language Study Program of Widyatama University always carries out Community Service Program (P2M) which is regularly held as a form of contribution to society. Through this activity, it is hoped that a good relationship will be established between the world of campus education and the community as well as a real form of concern.Knowledge about Japan is growing rapidly in Indonesia. This can be seen by the increasing number of Japanese learners both through academic channels ranging from high school to college or university level and also through course institutions that are growing and developing more and more in every major city in Indonesia. In addition, we can see knowledge about Japan from the increasing number of Japanese products entering Indonesia from various industrial sectors, ranging from the food industry to the entertainment industry, as well as the increasing number of Japanese companies opening factories in Indonesia.Referring to this, the Japanese Language Study Program at Widyatama University feels the need to participate in providing real assistance apart from being an educational institution that teaches Japanese as well as wanting to help people to know and understand more about Japan, not only in terms of language. In this case, we at the same time want to analyze the extent of public interest in knowledge of Japan, especially among students of 16 Bandung Public High School.